Potensi Pembangkit Listrik Tenaga Air Mikrohidro di Sungai Pintab dan Sungai Amandit Kalimantan Selatan - Rendi Rendi; Jainal Arifin; Mujiburrahman Mujiburrahman; Ice Trianiza (Proklamasi 45 University, 2020)
A survey of the potential for electricity generation from water energy was carried out on two rivers in South Kalimantan. These rivers are the Batang Banyu River or the Pintab River in Balangan Regency and the Amandit River in Kandangan Regency. The purpose of this study is to calculate the potential for electrical energy. The method used is to collect primary data in water velocity, cross-sectional river area, river discharge, and river height. Measurements were carried out three times at different times, namely in January, April, and July 2020. The difference in this month is due to the presence of the rainy season and the dry season. The method used in measuring river potential is measuring the river's flow rate. It is calculated by the potential energy equation, after obtaining the river's hydraulic potential, then calculating the generating power. Based on the calculations that have been made on the Batang Banyu River or the Pintab River in Balangan Regency and the Amandit River in Kandangan Regency, the potential for micro-hydropower plants is quite large, namely 419.7 kW and 619 kW, respectively. Suppose the river is installed with a turbine with an efficiency of 0.74, a generator efficiency of 0.85, and the mechanical transmission efficiency of 0.98, then the river respectively can generate electricity 258.71 kW and 360.9 kW.Survei potensi pembangkit listrik dari energi air dilakukan pada dua sungai di Kalimantan Selatan. Sungai tersebut adalah Sungai Batang Banyu atau Sungai Pintab di Kabupaten Balangan dan Sungai Amandit di Kabupaten Kandangan. Tujuan penelitian ini adalah untuk menghitung potensi energi listrik. Metode yang digunakan yaitu mengumpulkan data primer berupa kecepatan air, luas penampang sungai, debit sungai, dan ketinggian sungai. Pengukuran dilakukan sebanyak tiga kali dengan waktu yang berbeda yaitu pada bulan Januari, April, dan Juli 2020. Perbedaan bulan ini dengan pertimbangan adanya musim hujan dan musim kemarau. Metode yang digunakan dalam pengukuran potensi sungai adalah mengukur debit aliran sungai, kemudian dihitung dengan persamaan energi potensial. Setelah diperoleh potensi hidrolik sungai, kemudian menghitung daya pembangkit. Berdasarkan perhitungan yang telah dilakukan pada sungai Batang Banyu atau Sungai Pintab di Kabupaten Balangan dan Sungai Amandit di Kabupaten Kandangan, diperoleh potensi pembangkit listrik tenaga air mikrohidro cukup besar yaitu berturut-turut adalah 419,7 kW dan 619 kW. Apabila di sungai tersebut dipasang sebuah turbin yang memiliki efesiensi 0,74, efesiensi generator 0,85, dan efesiensi transmisi mekanik 0,98, maka sungai tersebut dapat membangkitkan listrik berturut-turut sebesar 258,71 kW dan 360,9 kW.